Conference proceedings : Enhancing financial sector soundness in Nigeria, 25-26th November, 2002 - Central Bank of Nigeria; Central Bank of Nigeria (Abuja : Central Bank of Nigeria, 2003)
The work contains seven papers on the following sub-themes: financial sector soundness, unsound banking system, liberalization and financial sector soundness, the legal framework and financial sector soundness and banking crisis.
Includes bibliographical references.
rua 24/11/16
Loans
Keywords: Monetary policy; Finance; Banks and banking; Financial sector; Nigeria